70 Assessing the impact of the covid-19 pandemic on rapid access chest pain clinics: a retrospective audit in glasgow. (6th June 2022) - Fernando, Julie; Lee, Matthew; Quinn, Dawn; Corcoran, David; Connolly, Eugene
Abstract : Introduction: Rapid Access Chest Pain Clinics (RACPCs) offer rapid, comprehensive assessment of patients presenting with chest pain and effectively identify low-risk and high-risk patients of a fatal coronary event, such as myocardial infarction (MI) and death. The COVID-19 pandemic in March 2020 has led to many clinic cancellations, face-to-face appointments being replaced by telephone consultations, and limited access to key investigations such as electrocardiogram (ECG) and exercise treadmill tests (ETT). The impact of the pandemic on this service has not been previously studied. The aim of this audit was to assess referral patterns from primary and secondary care settings to the NHS Greater Glasgow and Clyde (GGC) RACPC and compare clinical outcomes pre- and post-pandemic. Methods: Retrospective data was collected from a cohort of 90 patients attending three NHS GGC RACPCs between January 2019 to January 2021. The first consecutive 10 patients attending each month were analysed. Many RACPC clinics were closed in April 2020 onwards and therefore no data was available. Data was retrieved from NHS GGC electronic healthcare records at baseline and at one year follow-up. Patients were categorised into three subgroups based on the initial diagnosis made at the RACPC: acute coronary syndrome, stable coronary heart disease and low-risk/non-coronary chest pain. Statistical analysis was conducted using STATA. Results: Five out of the 90 patients did not attend their RACPC appointment. At baseline, co-morbidities included hyperlipidaemia (80%), hypertension (36%), diabetes (14%) and obesity (37%) (Table 1). In 2019 and 2020, most patients were diagnosed with low risk/non-coronary chest pain (68% and 78% respectively). In contrast, in January 2021, most patients were diagnosed with stable coronary heart disease (70%). Only one patient was diagnosed with acute coronary syndrome during this study period. In 2019 and 2020, almost all patients had ECGs, and many had ETTs performed on the same day as the initial RACPC assessment (Table 2). Whereas in 2021, time from initial RACPC appointment to investigation was longer (median 92.5 days for ECG and 21 days for ETT). More patients had myocardial perfusion scans (MPS) pre-pandemic compared to post-pandemic (p=0.035). In January 2020, 3 patients underwent PCI and of these, 2 patients had MIs before the percutaneous coronary intervention (PCI) procedure and were alive at follow-up (Table 2). In January 2019, one patient had coronary artery bypass graft (CABG) surgery. In 2021, no patients underwent coronary intervention (PCI or CABG) and there were no cases of MI or death during follow-up. The median time from referral to RACPC assessment was approximately 14 days or less. Patients in 2021 had earlier appointments compared to other years (median 7 days). Overall, patients assessed in 2020 had investigations earlier than other years, whilst patients in January 2021 waited the longest from initial assessment to investigations. Conclusion: In 2021, patients waited longer for investigations compared to previous years. This is likely due to the large backlog of patients due to clinic closures and reduced services during the pandemic. Also, in 2021 many patients were assessed via telephone (instead of face-to-face) consultations due to national/local restrictions. This may explain the high proportion of patients diagnosed as stable coronary heart disease in 2021 compared to previous years. Only one patient was categorised as 'acute coronary syndrome', and this patient underwent CABG within follow-up. No patients suffered an MI or died of cardiac causes. Our audit shows that patients in the medium and high-risk categories were effectively and safely triaged in the RACPC service. Since the pandemic, RACPC staff in Glasgow have noticed increasing numbers of patients with MI while waiting for their RACPC appointment. This was not evident in this audit, which may be due. Conflict of Interest: None